Quality of Life in Late-Treated Patients With Disorders of Sex Development: Insights for Patient-Centered Care - Ediati, Annastasia; Verrips, Gijsbert H. W.; Juniarto, Achmad Zulfa; Faradz, Sultana M. H.; Drop, Stenvert L. S.; Dessens, Arianne B. (Frontiers in Pediatrics, 2019)
ABSTRACT Background: Patients with a disorder of sex development (DSD) are born with atypical genitals or may develop atypical genitals and atypical body appearance, if left untreated. Health related quality of life (HRQoL) was assessed in Indonesian patients to whom diagnostic procedures and medical intervention had been delayed. Method: Comparison of 118 patients born with DSD, aged 6-41 years (60 children, 24 adolescents, and 34 adults) and 118 healthy control subjects matched for gender, age, and residential setting. HRQoL was measured using a translation of the TACQOL / TAAQOL. Results: According to parental and children’s report, children with DSD reported more problems in social functioning and had less positive moods. Particularly girls reported problems in cognitive functioning. Adult patients reported more depressive moods, especially women reported more anger moods. No differences were found between in the adolescent groups. Conclusion: Compared to non-affected Indonesians, Indonesians with DSD experienced more problems in social contacts and more often suffered from negative emotions. These findings on HRQoL are in line with findings on emotional functioning. Education on disease and coping strategies will facilitate patients’ empowerment. Such interventions can be offered by specialized teams and should be integrated into clinical management.